Paraliropus nom. nov., a replacement name for Pseudoliropus Guerra-García & Ahyong, 2020, preoccupied by Pseudoliropus Laubitz, 1970 (Crustacea: Amphipoda: Caprellidae) - José M. Guerra-García; Shane T. Ahyong (Records of the Australian Museum, 2021)
Guerra-García & Ahyong (2020) erected the genus Pseudoliropus (type species Pseudoliropus keablei Guerra-García & Ahyong, 2020) for a new species of caprellid amphipod from southern Australia. Shortly after publication the authors became aware that the genus name was preoccupied by the little known, caprellid Pseudoliropus Laubitz, 1970 (type species: Pseudoliropus vanus Laubitz, 1970). Although Pseudoliropus Laubitz, 1970 is not well diagnosed, and lacks figures and detailed description (Laubitz, 1970: 78; Laubitz 1993: 969; Takeuchi, 1993: 952), it is currently considered valid and remains nomenclaturally available. Pseudoliropus Guerra-García & Ahyong, 2020, therefore, is a junior homonym of Pseudoliropus Laubitz, 1970, and needs to be replaced under Article 60.1 of the International Code of Zoological Nomenclature (ICZN, 1999). Therefore, we propose Paraliropus nom. nov. to replace the preoccupied Pseudoliropus Guerra-García & Ahyong, 2020. The gender is masculine. The name is an arbitrary combination of the Greek παρά (para, meaning “near”, “next to”) and the caprellid genus name, Liropus, alluding to the similarity between members of Liropus and Paraliropus. At present, Paraliropus nom. nov., contains only the type species, Paraliropus keablei (Guerra-García & Ahyong, 2020) comb. nov.